DISCORDANT THYROID FUNCTION TESTS DUE TO DYSALBUMINEMIC HYEPRTHYROXINEMIA CONFOUNDS MANAGEMENT OF THYROID AUTOIMMUNITY - SSK, Khoo; G, Lyons; A, Solomon; S, Oddy; D, Halsall; K, Chatterjee; C, Moran (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Familial dysalbuminemic hyperthyroxinemia (FDH) is a cause of discordant thyroid function tests (TFT) due to interference in free thyroxine (FT4) assays caused by the mutant albumin. The coexistence of thyroid disease and FDH can further complicate diagnosis and potentially result in inappropriate management. We describe a case of Hashimoto’s thyroiditis and Graves’ disease occurring on a background of FDH. CASE A 42-year-old lady with longstanding autoimmune hypothyroidism was treated with varying dosages of thyroxine because of discordant TFTs, showing high (FT4) and normal thyroid stimulating hormone (TSH). Discontinuation of thyroxine led to marked TSH rise but with normal FT4 levels. She then developed Graves’ disease and thyroid ophthalmopathy, with markedly elevated FT4 (62.7 pmol/L), suppressed TSH (0.03 mIU/L) and positive anti-TSH receptor antibody levels. However, propylthiouracil treatment even in low dosage (100 mg daily) resulted in profound hypothyroidism (TSH 138 mIU/L, FT4 4.8 pmol/L), prompting its discontinuation and recommencement of thyroxine. Discordant thyroid hormone measurements using two different methods suggested analytical interference. Elevated circulating total T4 (TT4) [227 nmol/L, normal range (NR) 69 to 141] but normal thyroxine binding globulin (TBG) levels (19.2 µg/mL, NR 14.0 to 31.0) together with increased binding of patient’s serum to radiolabeled T4 suggested FDH. ALB sequencing confirmed a causal albumin variant (R218H). CONCLUSION This case highlights the difficulty in ascertaining true thyroid status in patients with autoimmune thyroid disease and coexisting FDH. Early recognition of FDH as a cause for discordant TFTs, with use of either TSH or FT4 measured by equilibrium dialysis as markers of true thyroid status, may improve patient management.